Socio-demographic characteristics of the mothers and infant feeding practices in some semi urban villages of a selected Upazilla - Mahejabin, Farzana; Khan, Abdul Wadud; Sultana, Masuda (Community Based Medical Journal, 2013)
To identify the socio-demogrsphic factors and to determine the breast-feeding and weaning practices of the mothers of infants in some selected villages of Dhamrai. A descriptive type of cross sectional study was conducted from July to December, 2011. A total of 320 mothers were interviewed having infant up to the age of 1 year. A validated questionnaire, which consists of questions relating to socio-demographic data, breast-feeding and weaning practices, was used. The total number of mothers interviewed was 320 who had infants up to 1 year of age. The mothers were mostly 154(48.1%) aged 21- 25 years and 107 (33.4%) aged 26-30 years. Most 151 (47.2%) of the mothers were educated up to primary level and 96(30%) up to secondary level. 71 mothers were illiterate. The mothers were mostly 190(55.4%) belonged to nuclear family and 129(40.3%) joint family. Most 301(94.1%) of the mothers were housewife. The monthly income of the respondents were Taka 5001-10000 amongst 149(47%) and Taka < 5000 132 (41%). The mean monthly family income of the respondents was 7626.56±3171.248 Taka. Out of 320 infants, 137 (43%) were aged 9-12 months, 124 (39%) were 6-9 months and 59 (18.4%) infants were aged < 6 months. The infants mostly 96(30%) weighted more than 8 kg, 95 (30%) weighted 6-8 kg and 76 (24%) weighted 4-6 kg. All the mothers had initiated breast feeding to their infants and majority 298(98%) were on breast feeding and 57 (96.6%) were on exclusive breast feeding during the study. The infants of < 6 months fed breast milk 8 times or more in a day, the infants of 6-9 months fed breast milk 6-8 times in a day and those not breast fed they fed liquid/soft foods 4-6 times in a day. The infants of 9-12 months fed breast milk 4-6 times in a day and those not breast fed they fed liquid/soft foods 6-8 times in a day. The infants mostly 57(96.6%) were on exclusive breast feeding at the age of <6 months and on complementary feeding 77 (62%) and 83(60.5%) infants at the age of 6-9 and 9-12 months respectively. The infants were not on breast feed 13 (10.5%) at the age of 6-9 months and 23(16.8%) at the age of 9-12 months. Out of 320 respondents 315(98.4%) were aware about the usefulness of breast feeding and 5(1.6%) were not aware. Out of 320 respondents 269(84.1%) were aware about the complementary food and 51(15.9%) were not aware. Out of 320 respondents 218(68.1%) were aware about the knowledge of starting weaning food and 102(31.9%) were not aware about the starting of weaning food. The results of the study indicate that the breast feeding practices among the mother of urban areas were well practiced. DOI: http://dx.doi.org/10.3329/cbmj.v2i1.14183 Community Based Medical Journal Vol.2(1) 2013 43-48